1999
DOI: 10.1007/bf03190366
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lidocaine metabolism by rat nasal microsomes: implications for nasal drug delivery

Abstract: Lidocaine has been recently approved for use as an intranasal spray in the treatment of migraine. In this study, we investigated the metabolism of lidocaine to its primary metabolite monoethylglycine xylidide (MEGX), by rat nasal olfactory and respiratory microsomes. The metabolic parameters were compared with metabolism employing rat and human hepatic microsomes. The olfactory and respiratory microsomes both exhibited considerable activity for conversion of lidocaine to MEGX in comparison with the activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Antibodies raised against CYP2A (Su et al, 1996) or CYP2B (Wardlaw et al, 1998) have been used in OM, but their lack of specificity precluded accurate P450 identification. Even after a 35-cycle amplification, we did not observe any expression of mRNA coding for CYP2C6, 2C11, 2D2, 3A1, 3A2, and 4A1 in OM, although Western blot experiments showed that CYP2C11 and 3A2 proteins were present in very low quantities in OM (Deshpande et al, 1999;Genter et al, 2002). The conflicting results concerning CYP3A may be explained by the observations of Aiba et al (2003): their work demonstrated the existence of an immunological cross-reaction between CYP3A2 and CYP3A9; the mRNA of the latter was clearly detected in OM in the present study.…”
Section: Downloaded Fromcontrasting
confidence: 57%
See 2 more Smart Citations
“…Antibodies raised against CYP2A (Su et al, 1996) or CYP2B (Wardlaw et al, 1998) have been used in OM, but their lack of specificity precluded accurate P450 identification. Even after a 35-cycle amplification, we did not observe any expression of mRNA coding for CYP2C6, 2C11, 2D2, 3A1, 3A2, and 4A1 in OM, although Western blot experiments showed that CYP2C11 and 3A2 proteins were present in very low quantities in OM (Deshpande et al, 1999;Genter et al, 2002). The conflicting results concerning CYP3A may be explained by the observations of Aiba et al (2003): their work demonstrated the existence of an immunological cross-reaction between CYP3A2 and CYP3A9; the mRNA of the latter was clearly detected in OM in the present study.…”
Section: Downloaded Fromcontrasting
confidence: 57%
“…In OM, we detected the mRNA coding for CYP1A1, 1A2, 2A3, 2E1, 2G1, 2J4, and 4B, the expression of which had already been described by others at the protein level (Chen et al, 1992;Zhang et al, 1997;Wardlaw et al, 1998;Deshpande et al, 1999;Genter et al, 2002) or at the mRNA level (Nef et al, 1989;Zhang et al, 1997;Longo et al, 2000;Wang et al, 2002;Robottom-Ferreira et al, 2003). In addition, we identified for the first time the mRNA coding for CYP2A1, 2B2, 2B21, 2D1, 2D4, and 3A9.…”
Section: Downloaded Fromsupporting
confidence: 55%
See 1 more Smart Citation
“…We recently showed that metabolism of lidocaine to MEGX was catalyzed by microsomes prepared either from nasal olfactory or respiratory mucosa [21]. This was of interest to us for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…However, most substrate probes of the CYP450 superfamily are non-specific for the recognition of the enzymes although selectivity is apparent for some compounds (6)(7); and the majority of CYP450s expressed in the hepatic microsome have been found in extrahepatic tissues (8)(9)(10), where xenobiotics are transformed into active intermediates or inactive metabolites as in liver. So far, the metabolic capacity of phenacetin O-deethylase(s) in the extrahepatic tissues is unknown for lack of a suitable methodology.…”
Section: Introductionmentioning
confidence: 99%